Reflections on 10 years of effectiveness-implementation hybrid studies - Curran, Geoffrey M.; Landes, Sara J.; McBain, Sacha A.; Pyne, Jeffrey M.; Smith, Justin D.; Fernandez, Maria E.; Chambers, David A.; Mittman, Brian S. (Frontiers in Health Services, 2022)
This article provides new reflections and recommendations from authors of the initial effectiveness-implementation hybrid study manuscript and additional experts in their conceptualization and application. Given the widespread and continued use of hybrid studies, critical appraisals are necessary. The article offers reflections across five conceptual and methodological areas. It begins with the recommendation to replace the term “design” in favor of “study.” The use of the term “design” and the explicit focus on trial methodology in the original paper created confusion. The essence of hybrid studies is combining research questions concerning intervention effectiveness and implementation within the same study, and this can and should be achieved by applying a full range of research designs. Supporting this recommendation, the article then offers guidance on selecting a hybrid study type based on evidentiary and contextual information and stakeholder concerns/preferences. A series of questions are presented that have been designed to help investigators select the most appropriate hybrid type for their study situation. The article also provides a critique on the hybrid 1-2-3 typology and offers reflections on when and how to use the typology moving forward. Further, the article offers recommendations on research designs that align with each hybrid study type. Lastly, the article offers thoughts on how to integrate costs analyses into hybrid studies.